Mapping information research in Canada - Mongeon, Philippe; Gracey, Catherine; Riddle, Poppy; Hare, Madelaine; Simard, Marc-André; Sauvé, Jean-Sébastien (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2023)
This study examines the Canadian information research landscape through the lens of the eight academic units hosting ALA-accredited programs. We created a citation-based network utilizing the scholarly articles published by the faculty members and PhD students at each academic unit to identify and characterize distinct research clusters within the field. Then we determined how the publications and researchers from each unit are distributed across the clusters to describe their area of specialization. Our findings emphasize how the inter-, multi-, and transdisciplinary nature of the Canadian information research landscape forms a rich mosaic of information scholarship.